The Development Of Waqf Properties By Using Creditbased Financing Methods:A Critical Review And Its Implications To Social Welfare Of The Ummah - Omar, Hydzulkifli Hashim; Ahmed, Umar; Md Jadi, Diara (Universiti Sains Islam Malaysia, 2024)
Waqf properties constitute a large percentage of societal wealth in several Muslim countries. Yet, numerous Muslim countries are facing enormous socio-economic problems such as poverty, illiteracy and lack of basic healthcare services. This encourages contemporary Muslim scholars to formulate new financing methods that can be used to develop Waqf properties and ensure that these modes conformed with the Shariah. These methods are grouped into three, namely: credit-based financing, institutional financing and corporatebased financing. Indeed, the applications of some of these financing methods have been proven successfully in the development of Waqf properties. This paper attempts to critically review credit-based financing methods to aid the development of Waqf assets and their implications on the social welfare of the ummah. We realized that some of the credit based methods such as Build-Operate-Transfer and many of its variance are not suitable in developing Waqf assets, which require that the method will generate sufficient income to meet urgent social needs of society. There is no income guarantee with most of these credit– based contracts. Infact, the financier or developer will own the building (usufruct) for a long leasing period and by the time they sell or transfer the building to Waqf institution, the building will be old, dilapidated and its value depreciated; thus it defeats the very basic notion of improving social welfare of the people.